Fatores associados à atividade física em pessoas idosas brasileiras com e sem DCNT : uma análise da PNS 2019 - Pereira, Zainovan Serrão (2023)
The study aimed to analyze whether sociodemographic factors and health risk behaviors are associated with physical activity in older adults with and without non-communicable chronic diseases (NCDs). Methods: A cross-sectional study using data from the National Health Survey of 2019 was conducted. The sample consisted of older individuals (≥60 years old), totaling 22,726 people. The study outcome was physical activity during leisure time. The independent variables were: gender; age; ethnicity; marital status; region of residence; education level; per capita income; and variables related to health risk behaviors: self-perceived health; dietary habits; television viewing time; and nutritional status. The variable NCD was used to divide the sample into older adults with and without NCDs. Binary logistic regression for complex samples was used, adopting a significance level of p≤0.05. For statistical analysis, Stata® software version 16.0 was used. Results: Male gender (OR = 1.25; 95% CI = 1.05;1.48); residing in the Northeast region (OR = 1.26; 95% CI = 1.04;1.53); having completed higher education (OR = 1.92; 95% CI = 1.48; 2.49); income higher than three minimum wages (OR = 1.86; 95% CI = 1.33; 2.60); and dietary habits (OR = 1.05; 95% CI = 1.04; 1.07) were associated with being physically active in the group without NCDs. In the group with NCDs, having completed higher education (OR = 4.09; 95% CI = 2.92; 5.62); income higher than three minimum wages (OR = 1.64; 95% CI = 1.09; 2.48); and dietary habits (OR = 1.03; 95% CI = 1.01; 1.05) were associated with engaging in physical activity. Age of individuals in the groups without NCDs (OR = 0.97; 95% CI = 0.96; 0.98) and with NCDs (OR = 0.96; 95% CI = 0.94; 0.97); and reporting regular self-perceived health in the group with and without NCDs (OR = 0.53; 95% CI = 0.43; 0.66 versus OR = 0.61; 95% CI = 0.52; 0.73), were associated with physical inactivity. Conclusion: Gender, region, education level, income, and dietary habits were associated with being physically active in the group without NCDs. While educational level, income, and dietary habits were related with being physically active in the group with NCDs. Age and selfperceived health were related with physical inactivity in both groups.